Exaggerated sexually selected weapons maintained with disproportionately low metabolic costs in a single species with extreme size variation. (12th August 2021) - Somjee, Ummat; Powell, Erin C.; Hickey, Anthony J.; Harrison, Jon F.; Painting, Christina J.
Abstract: Larger individuals typically have lower mass‐specific metabolic rates compared to small ones (hypometric scaling). This trend is most evident across species where body size differences can be extreme. Yet, within‐species studies are critical to decipher the morphological and physiological mechanisms responsible. However, in most species, the relatively small range in body and appendage size of the same life stage often precludes such intraspecific comparisons. Sexually selected weapons are among the most exaggerated traits in nature; these traits can account for a large portion of body mass and contribute to whole‐body energetic maintenance costs. Often larger individuals possess disproportionally larger weapons relative to their body size, yet little is known about how large individuals meet the predicted increased energetic demands of maintaining disproportionately large weapons. New Zealand giraffe weevils, Lasiorhynchus barbicornis (Coleoptera: Brentidae) exhibit an extreme 30‐fold range in male body mass as well as hypermetric scaling of sexually selected rostra used as weapons in male–male competition. We compare intra‐ and interspecific resting metabolic rates by compiling measurements across 26 arthropod species whose size ranges overlap with L. barbicornis . The scaling of metabolic rate across this pooled interspecific sample was not significantly different from the intraspecific scaling of metabolic rate we found in L. barbicornis (slope of log–log relationship with body mass = 0.67). Male and female L. barbicornis had a similar scaling of metabolic rate with body size, despite differing substantially in the scaling of rostra, legs and antennae. However, large structures that scaled with positive allometry in males (rostra and legs) were increasingly composed of cuticle in larger individuals. The largest males invest ~60% less metabolically active tissue into rostra (weapons) compared to the smallest males. Our findings reveal hypometric scaling relationships of inter‐ and intraspecific metabolic rates across a shared size range in a diverse group of arthropods. Our intraspecific study uncovers a tremendous difference in weapon architecture as individuals scale up in size; we find that large males bear disproportionally larger weapons at a lower relative metabolic cost. This cost‐saving mechanism may play a key role in shaping the hypermetric scaling of sexually selected traits. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Resumen: Los individuos más grandes tienden a tener tasas metabólicas relativas más bajas en comparación con individuos de menor tamaño (escala hipométrica). Esta tendencia se hace más evidente entre especies donde las diferencias en el tamaño del cuerpo pueden ser extremas. Para entender los mecanismos morfológicos y fisiológicos responsables es importante realizar estudios intra‐específicos, sin embargo en muchas especies la variación en el tamaño del cuerpo y los apéndices entre individuos adultos es muy baja, lo que dificulta este tipo de comparaciones. Las armas bajo selección sexual se cuentan entre los rasgos más exagerados en la naturaleza, estos rasgos pueden representar una gran parte de la masa corporal y contribuir a los costos de mantenimiento energético de todo el cuerpo. A menudo, los individuos más grandes poseen armas desproporcionalmente más grandes en relación a su cuerpo. Sin embargo, se sabe poco sobre cómo los estos individuos logran satisfacer las demandas energéticas mayores para mantener estas armas desproporcionadamente grandes. El gorgojo jirafa de Nueva Zelanda Lasiorhynchus barbicornis (Coleoptera: Brentidae), tiene un rango extremo (30 veces) en la masa corporal entre machos adultos y un escalamiento hipermétrico de la rostra, la cual está bajo selección sexual y es usada como arma en la competencia entre machos. Comparamos las tasas metabólicas en reposo intra e interespecíficas de 26 especies de artrópodos cuyos rangos de tamaño traslapanel de con L. barbicornis . La escala de la tasa metabólica en esta muestra interespecífica combinada no fue significativamente diferente de la escala intraespecífica de la tasa metabólica que encontramos en L. barbicornis (pendiente de la relación log‐log con la masa corporal = 0.67). Los machos y las hembras de L. barbicornis tenían una escala similar de tasa metabólica con el tamaño corporal, a pesar de diferir sustancialmente en la escala de rostra (armas), patas y antenas. Sin embargo, las grandes estructuras con alometría positiva en los machos (rostra y patas) se componían más de cutícula en individuos más grandes. Los machos más grandes invierten ~60% menos de tejido metabólicamente activo en rostra (armas) en comparación con los machos más pequeños. Descubrimos relaciones de escala hipométrica en las tasas metabólicas inter e intraespecíficas entre un grupo diverso de artrópodos dentro de un mismo rango de tamaño. Nuestro estudio intraespecífico revela una enorme diferencia en la arquitectura de las armas a medida que los individuos aumentan de tamaño; encontramos que los machos grandes llevan armas desproporcionadamente más grandes con un costo metabólico relativo más bajo. Este mecanismo de ahorro de costos puede desempeñar un papel clave en la configuración de la escala hipermétrica de los rasgos seleccionados sexualmente.